Analisis Perkembangan Pembayaran Sistem Non Tunai Di Era 4.0 (QRIS) Di Kota Palangka Raya - Muhammad Farras Nasrida; Melya Nanda (Dharma Ekonomi, 2023)
This istudy aimsi to analyze thei development of the usei of a non-cashi payment systemi using QRIS in thei City of Palangka Raya ini the erai of theiindustrial 4.0. Theimethod usediis aisurvey through questionnaires to users and merchants who use QRIS as a payment system. Thei collected datai were analyzedi using descriptiveistatistical techniquesiand factorianalysis toiidentify theifactorsithat influenceithe useiof QRISiin Palangkai RayaiCity. The results of the study show that the use of QRIS in Palangka Raya City has experienced significant developments in the last two years. Factorsithat influenceithe use ofi QRISi are ease of use, transaction security, and financial benefits. The implication ofi the resultsi of thisi study isi that therei is a needi to improve education andi outreach about using QRIS as an alternative to non-cash payment systems in Palangka Raya City.